SERUM VITAMIN A LEVELS IN CHILDREN UNDER FIVE YEARS OLD - Rauf, Shahid; Sharif, Nasreen; Hamid, Abdul (Journal of Ayub Medical College Abbottabad, 2002)
Background: Vitamin A deficiency is considered to be a wide spread public health problem among preschool children in the developing countries. A pilot study for the nutritional problems in Pakistan showed that majority of the children in the study group was suffering from vitamin A deficiency. Methods: This study was carried out to assess the vitamin A status of children under five belonging to different socioeconomic groups. They were divided into two groups. Their weight for age criterion fell within the reference range set by Pakistan Pediatric Association in accordance with National Center for Health Statistics. The vitamin A levels were determined spectophotometrically by using trifluoroacetic acid. Results and Conclusion: The results suggested a significant difference in the levels of Vitamin A in children belonging to high and low socioeconomic groups, suggesting the role of socioeconomic factors in determining the vitamin A status of the body.